Human leptospirosis: seroreactivity and genetic susceptibility in the population of São Miguel Island (Azores, Portugal). - Lisa M Esteves (Public Library of Science (PLoS), 2014)
Background Leptospirosis is a worldwide zoonotic and recognized neglected infectious disease. It has been observed that only a proportion of individuals exposed to pathogenic species of Leptospira become infected and develop clinically evident disease. Moreover, little information is available in subsequent reinfections. In the present study, we determine if a first infection with leptospirosis protects against subsequent reinfection, and investigate which of the host genetic factors are involved in the susceptibility and resistance to leptospirosis. Methodology and findings We conducted, in 2011, a retrospective hospital-based case-control study in the São Miguel Island population (Azores archipelago). In order to determine the seropositivity against pathogenic Leptospira after the first episode of leptospirosis, we performed a serological evaluation in 97 unrelated participants diagnosed with leptospirosis between 1992 and 2011. The results revealed that 46.4% of the 97 participants have circulating anti-Leptospira antibodies, and from these participants 35.6% maintained the seroprevalence for the same serogroup. Moreover, three of them were reinfected with unrelated Leptospira serovars. The genetic study was carried out by adding a control group composed of 470 unrelated healthy blood donors, also from São Miguel Island. Twenty five SNPs among twelve innate immune genes - IL1α, IL1β, IL6, IL10, IL12RB1, TLR2, TLR4, TLR9, CD14, CISH, LTA and TNF - were genotyped, as well as HLA class I (-A and -B) genes. Association analysis indicates that genotypes -511GG (OR=1.6, 95%CI 1.01-2.56, p=0.04) in IL1β, +1196CG (OR=2.0, 95%CI 1.26-3.27, p=0.003) in IL12RB1, -292TA (OR=1.8, 95% CI 1.06-2.1, p=0.03) and +3415CG (OR=1.8, 95% CI 1.08-3.08, p=0.02), both in CISH confer susceptibility to pathogenic Leptospira. Conclusion The present study suggests some degree of long-term protection against leptospires with an attenuation of symptoms in case of reinfection. Moreover, our data supports the genetic influence of IL1β, IL12RB1 and CISH genes and the susceptibility to leptospirosis infection.